(untitled) (Blockchain Technology and Distributed Systems, 2021)
Blockchain technology has revolutionized various industries by offering decentralized and secure transaction systems. A key component of blockchain networks is the consensus mechanism, which ensures agreement among nodes on the validity of transactions. This paper provides a comprehensive analysis of three prominent consensus mechanisms: Proof of Work (PoW), Proof of Stake (PoS), and Practical Byzantine Fault Tolerance (PBFT). We discuss the underlying principles, advantages, and limitations of each mechanism, along with real-world implementations. By comparing these mechanisms, we aim to provide insights into their suitability for different blockchain applications and the evolution of consensus mechanisms in blockchain networks.